Assessing the long-term persistence of SARS-CoV-2 in Guinea: insights from post-epidemic sentinel syndromic surveillance data - Kadio, Kadio Jean Jacques Olivier; Gnimadi, Thibaut Armel Chérif; Guichet, Emilande; Hounmenou, Castro Gbêmemali; Soumah, Abdoul Karim; Diallo, Haby; Camara, Amadou; Camara, Saidouba Chérif; Sandouno, Marie Rose; Bangoura, Salifou Talassone; Diaby, Maladho; Richard, Vincent; et al. (Frontiers in Epidemiology, 2025)
BackgroundIn December 2019, the world experienced one of the significant health crises of the 21st century with the emergence and rapid spread of the potentially fatal 2019 coronavirus (COVID-19). In this context, sentinel surveillance of SARS-CoV-2 variants was conducted in Conakry. Here we report the first data on reproduction numbers and risk factors during the Omicron post-epidemic period in Guinea.MethodsA sentinel syndromic and genomic surveillance study was conducted on suspected patients from October 2022 to July 2024 at healthcare facilities in Conakry. Individual data and nasopharyngeal swabs were collected and sent to the Centre de Recherche et de Formation en Infectiologie de Guinée (CERFIG) laboratory for screening and sequencing by next-generation sequencing (NGS). The effective reproduction number (Rt) were estimated using EpiEstim to assess the transmission potential of the Omicron variant. Generalized linear models based on the binomial distribution were employed to analyze factors associated with SARS-CoV-2 positivity, following the identification of primary risk factors using Bayesian model averaging and the Data balancing algorithm using propensity score matching.ResultsData from 1174 patients with suspected cases with a median age of 31 years (IQR: 20–51), were analyzed. The overall COVID-19 positivity rate was 11.8%. The global effective reproduction number (Rt) was 2.08 [95% CI: 0.35–5.81]. Only ageusia [AOR = 2.0; 95% CI (1.1–3.6)] was independently associated with SARS-CoV-2 test positivity.ConclusionSARS-CoV-2 is still circulating in Guinea, with a high positivity rate and a high number of effective reproductions in this post-epidemic period in our country. The associated factors and the circulation of variants with a diversity of circulating strains suggest the need to strengthen genomic and epidemiological surveillance, with the support of all those involved in the response to COVID-19, to ensure continuity of alerts and decision-making for public health.